Two (2) Degree of Freedom (DOF) flight simulator platform / Mohd Aswad Othman … [et al.] - Othman, Mohd Aswad; Muhammad Khairi, Muhammad Mahsyar; Syed Kharuddin, Syed Ahmad Bukhary; Mazlan, Muhammad 'Arif; Khafizan, Fatin Aizat; Zhian Wei, Lim (Division of Research and Industry Linkages, 2017)
Conventional flight simulator platform currently used in the aviation industry is expensive and therefore not many institutions, private aviation entity or aviation enthusiasts can afford to own such machinery to be used as an aviation training kit. The aim o f this study is to propose a new design of flight simulator platform which is affordable, portable and easy to be built. The study will also serve as a guideline for aviation enthusiasts to build their own personal two (2) degree of freedom flight simulator platform.